PWE-048 Gastric volume response and emptying after a large liquid nutrient meal in functional dyspepsia and health assessed by non-invasive gastric scintigraphy (GS) and MRI: a pilot study to identify candidate biomarkers. (28th May 2012) - Tucker, E; Parker, H; Hoad, C; Hudders, N; Perkins, A; Blackshaw, P E; Marciani, L; Costigan, C; Gowland, P; Fox, M
Abstract : Introduction: Dyspeptic symptoms are common but investigations rarely explain them. This lack of information may be because: (1) Current test meals are small (∼200 ml) and don't trigger symptoms (2) gastric emptying half time (T50) and/or retention at 2 or 4 h may not elicit underlying pathophysiology. By contrast, MRI studies suggest that gastric volume change after a meal may identify impaired accommodation in functional dyspepsia (FDs). Aim: GS and MRI with a 400 ml liquid test meal were applied to identify candidate biomarkers that distinguish FDs from healthy volunteers (HVs). Methods: FDs with postprandial distress by Rome III criteria and normal endoscopy or 24 h pH-studies were recruited. Results were compared to age and sex matched HVs. Sensation at 400 ml and Maximum Tolerated Volume (MTV) was assessed by nutrient drink test (0.75 kcal/ml@40 ml/min). Participants were then randomised to GS and MRI with 400 ml liquid test meal (0.75 kcal/ml@40 ml/min) on two separate days. Directly comparable measurements of gastric content volume were analysed: Gastric contents volume after meal ingestion (GCV0), GE half-time [T50], and GErate@T50 [ml/min]. Results: FDs (n=8; 7 female) were each compared to those of three matched HVs (n=24). HVs weighed more than FDs (p<0.018) fullness at 400ml was similar (p=0.21) but dyspeptic sensations were lower (bloating, nausea, pain, p<0.01) and MTV was greater (median 960 (IQR 750–1330) vs 480 (±400–760) ml, p=0.015). With GS, HVs had higher GCV0 than FDs (345 (333–358) vs 325 (310–350) ml; p=0.052), T50 (48 (39–56) vs 52 (44–54) min; p=0.710) was similar but GErate@T50 was faster (3.5 (3.0–4.2) ml/min vs 2.7 (2.1–3.1) ml/min; p=0.012). With MRI, compared to GS, measurements of GCV and T50 were larger (p<0.001), and GErate was slower (p=0.012); but no significant differences between groups. Conclusion: FD patients are characterised by abnormal gastric sensorimotor response to a large, liquid nutrient meal. Rapid early emptying (reduced GCV0) is followed by slow late emptying (slow GErate@T50 ). These GS measurements, with dyspeptic symptoms at 400 ml, are biomarkers in FD. MRI measurements of GCV, residual volume, meal and secretions do not provide the same clarity. These findings are consistent with the hypothesis that impaired accommodation in gastric filling in FD leads to rapid nutrient delivery to small bowel triggering powerful neuro-hormonal feedback that slows subsequent emptying. Competing interests: None declared.